Feedlot performance, carcass characteristics and meat quality of Nellore bulls and steers fed Zilpaterol hydrochloride - Costa, C. F. [UNESP]; Brichi, A. L.C. [UNESP]; Millen, D. D. [UNESP]; Goulart, R. S.; Pereira, I. C. [UNESP]; Estevam, D. D. [UNESP]; Perdigão, A. [UNESP]; Martins, C. L. [UNESP]; Arrigoni, M. D.B. [UNESP] (Elsevier, 2019)
This study aimed to determine the effects of zilpaterol hydrochloride (ZH) on feedlot performance, carcass traits, feeding behavior and meat quality characteristics of Nellore steers and bulls. This study was conducted at the São Paulo State University (UNESP) feedlot, Botucatu Campus, Brazil. Seventy-two 18-month-old Nellore cattle from the same cattle herd, 36 steers and 36 bulls, were selected for this study. The experiment had a randomized block design based on the animals’ initial BW, in a 2 × 2 factorial arrangement of treatments, in which the factors were ZH addition to the diet (0 or 7.5 mg of ZH/ kg of feed 20 d prior to slaughter; ZILMAX® MSD Animal Health, São Paulo, SP, Brazil) and gender (bulls or steers). The 24 pens were considered the experimental units in this study, and each treatment was replicated six times (n = 3 per pen). Cattle were fed for 112 days, and the addition of 7.5 mg of ZH/ kg of feed was done for 20 d prior to slaughter (from day 90 to day 109). A withdrawal period of three days before slaughter was respected (from day 110 to 112). During the period of ZH supplementation, cattle fed ZH presented greater final BW (516.45 vs. 512.50 kg; P ≤ 0.001), ADG (1.73 vs. 1.32 kg; P ≤ 0.001), and improved G:F by 38.1% (0.187 vs. 0.135; P ≤ 0.001), when compared to cattle not fed ZH. Nellore steers receiving ZH reduced DMI by 9% when compared to steers not fed ZH (P = 0.04); however, Nellore bulls had similar intake regardless of ZH supplementation. Overall, cattle receiving ZH improved G:F by 6.6% (0.161 vs. 0.151; P = 0.03) and increased final LM area (79.32 vs. 76.30 cm2; P = 0.04), HCW (292.75 vs. 280.00 kg; P < 0.001), and dressing percentage (56.68 vs. 55.14; P < 0.001). The interaction between ZH supplementation and gender was observed (P = 0.02) for 12th rib fat daily gain in which steers decreased their rate of fat deposition when fed ZH, but no effect was observed for bulls. A significant increase was observed (4743.12 vs. 4286.23 µm2; P = 0.03) in the average area of Semitendinosus muscle fibers of cattle supplemented with ZH; however, no main effect of ZH supplementation was observed for final marbling (P = 0.27) or shear force (P = 0.20). Overall, ZH increased performance and hot carcass weight of Nellore cattle regardless of gender. In addition, supplementation of ZH lead to similar feedlot performance and meat quality between Nellore steers fed ZH and Nellore bulls not consuming ZH.
Keywords: Bulls; Feedlot; Nellore; Performance; Steers; Zilpaterol